Siglec‐G Suppresses CD8+ T Cells Responses through Metabolic Rewiring and Can be Targeted to Enhance Tumor Immunotherapy - Shenhui Yin; Chunzhen Li; Xin Shen; Guanyu Yu; Likun Cui; Yunyang Wu; Yixian He; Shu Yu; Jie Chen; Shaoteng Lu; Guifang Qiu; Mengqi Song; et al. (Advanced Science)
Abstract CD8+ T cells play a critical role in cancer immune‐surveillance and pathogen elimination. However, their effector function can be severely impaired by inhibitory receptors such as programmed death‐1 (PD‐1) and T cell immunoglobulin domain and mucin domain‐3 (Tim‐3). Here Siglec‐G is identified as a coinhibitory receptor that limits CD8+ T cell function. Siglec‐G is highly expressed on tumor‐infiltrating T cells and is enriched in the exhausted T cell subset. Ablation of Siglec‐G enhances the efficacy of adoptively transferred T cells and chimeric antigen receptor (CAR) T cells in suppressing solid tumors growth. Mechanistically, sialoglycan ligands, such as CD24 on tumor cells, activate the Siglec‐G‐SHP2 axis in CD8+ T cells, impairing metabolic reprogramming from oxidative phosphorylation to glycolysis, which dampens cytotoxic T lymphocyte (CTL) activation, expansion, and cytotoxicity. These findings discover a critical role for Siglec‐G in inhibiting CD8+ T cell responses, suggesting its potential therapeutic effect in adoptive T cell therapy and tumor immunotherapy.